ENHANCING EFL/ESL VOCABULARY LEARNING THROUGH WORDWALL-BASED GAMIFICATION: A SYSTEMATIC REVIEW OF COGNITIVE AND AFFECTIVE OUTCOMES IN EDUCATIONAL TECHNOLOGY RESEARCH - Nilna Afiyah; Tiyas Saputri; Mujad Didien Afandi; Novi Rahmania Aquariza (Universitas PGRI Palembang, 2026)
The growing incorporation of gamification and interactive digital platforms has become a pivotal development in English vocabulary instruction across EFL/ESL settings. Among these emerging tools, Wordwall has attracted considerable scholarly attention due to its capacity to foster engaging, technology-mediated learning experiences. This study seeks to critically synthesize recent empirical and review-based literature on the effectiveness of Wordwall and gamified instructional strategies in vocabulary acquisition. Employing a systematic literature review methodology, the analysis draws on studies presented in the provided literature tables, with particular emphasis on cognitive learning outcomes, affective dimensions, and prevailing methodological approaches. The findings consistently demonstrate that Wordwall-supported gamification enhances vocabulary mastery, improves retention and recall, and contributes to higher levels of academic achievement across diverse educational contexts. Moreover, affective factors such as learner motivation, enjoyment, active engagement, classroom participation, and positive attitudes toward learning emerge as key determinants of instructional success. The review also underscores the increasing relevance of educational technology and game-based learning in advancing interactive, student-centered vocabulary instruction. Overall, the evidence suggests that Wordwall holds substantial pedagogical value for contemporary EFL/ESL vocabulary learning environments.